Applied soil chemistry - Inamuddin, 1980-; Ahamed, Mohd Imran; Boddula, Rajender; Altalhi, Tariq (Scrivener Publishing ; John Wiley & Sons, Inc., 2021)
"This book explores the state-of-the-art information regarding applied soil sciences. It covers the fundamentals, model concepts, principles, chemical reactions, functions, chemical recycling, chemical weathering, acid-base chemistry, carbon sequestration, and nutrient availability of soils. Also, it includes soil chemistry of heavy-metals, environment, clay, ion-exchange processes, analytical tools and applications. This book helps to understand the about soil characteristics targeting soil chemical reactions and interactions and its applications."--